Discourse Analysis of Cross-Cultural Competencies in International Business Management - Nana Osei-Bonsu (European Scientific Journal, ESJ, 2016)
A broad range of literature available discusses the activities to prepare managers for becoming cross-culturally competent. In keeping up with the increased emphasis of cultural competences in the international business management, the major question is, what kind of cross cultural competencies would make firm managers better to respond to the whole range of challenges that globalization offers?. Consequently, this paper has reviewed the concept of culture in the literature through discourse analysis and found that in the field of international business management, the concept of cross-cultural competence is still viewed as the skill or ability of providing effective cross-cultural interactions and the ability of the business to function effectively in different culture environment. Discourse analysis is a qualitative research approach that offers the potential to challenge our thinking about the reality of culture in any social settings.